A Comparative Study Between ADM and MDM for a System of Volterra Integral Equation - Sizar Mohammed; Hela Ahmed (Jurnal Matematika MANTIK, 2021)
In this paper, a comparative study between Adomain decomposition method (ADM) and Modified decomposition method (MDM) for a system of volterra integral equation. From the illustrate examples it is observed that the exact solution is smaller in both methods, the modified decomposition method is more proficient than its traditional ones it is less complicated, needs less time to get to the solution and most importantly the exact solution is achieved in two iterations.